2023
DOI: 10.1002/qua.27188
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian expansion of Yukawa non‐local kinetic energy functionals: Application to metal clusters

Abstract: The development of kinetic energy (KE) functionals is one of the current challenges in density functional theory (DFT). The Yukawa non‐local KE functionals [Phys. Rev. B 103, 155127 (2021)] have been shown to describe accurately the Lindhard response of the homogeneous electron gas (HEG) directly in the real space, without any step in the reciprocal space. However, the Yukawa kernel employs an exponential function which cannot be efficiently represented in conventional Gaussian‐based quantum chemistry codes. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Recently, they proposed an expansion of the Yukawa kernel in Equation 16in terms of Gaussian functions in order to facilitate an implementation in quantum-chemical program packages using Gaussian-type orbitals as basis functions. 63…”
Section: Decomposable Approximationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, they proposed an expansion of the Yukawa kernel in Equation 16in terms of Gaussian functions in order to facilitate an implementation in quantum-chemical program packages using Gaussian-type orbitals as basis functions. 63…”
Section: Decomposable Approximationsmentioning
confidence: 99%
“…They showed that such functionals are able to accurately model the linear response of the electron gas and obtained promising results for rare‐gas atoms as well as jellium clusters. Recently, they proposed an expansion of the Yukawa kernel in Equation in terms of Gaussian functions in order to facilitate an implementation in quantum‐chemical program packages using Gaussian‐type orbitals as basis functions 63 …”
Section: Fundamentals Of Subsystem‐density Functional Theorymentioning
confidence: 99%
“…Recently, they proposed an expansion of the Yukawa kernel in Eq. 16 in terms of Gaussian functions in order to facilitate an implementation in quantum-chemical program packages using Gaussian-type orbitals as basis functions [63].…”
Section: While Most Of the Work Reviewed In Thismentioning
confidence: 99%
“…Recently, they proposed an expansion of the Yukawa kernel in Eq. 15 in terms of Gaussian functions in order to facilitate an implementation in quantum-chemical program packages using Gaussian-type orbitals as basis functions [63].…”
Section: Overview Of Recent Developments In Subsystemmentioning
confidence: 99%